A DESIGN OF SOCIAL MEDIA ANALYSIS SYSTEM BASED ON MOBILE PLATFORMS - ALAYBEYOGLU, Aysegul; YAVUZ, Levent (The Eurasia Proceedings of Educational and Social Sciences, 2017)
Along with the developing technology, social media technologies have become widespread and the number of internet users has increased rapidly. In addition, social media platforms have become very popular and the number of active social media users has increased considerably. As a result of the increased use of social media, there has been a trend towards mobile platforms. In this paper, a design of a social media analysis system is developed using mobile platforms based on Android. By this way, important data about social media users will be able to gathered and analysed.